2020
DOI: 10.1002/net.21995
|View full text |Cite
|
Sign up to set email alerts
|

Recent challenges in Routing and Inventory Routing: E‐commerce and last‐mile delivery

Abstract: In the e‐commerce era, vendors have to satisfy a large number of on‐line orders, mainly from private customers, with low weight and volume, reduced delivery time, and overlap of customers' time windows. Production is made available all day long. New strategies and new technologies are emerging for deliveries. The processing time of the orders is reduced. These new features generate interesting challenges in formulating and solving Routing and Inventory Routing problems. After discussing these features and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 93 publications
0
20
0
2
Order By: Relevance
“…Cattaruzza et al [22] surveyed the vehicle routing problems found in cities for good distribution and identified the important challenges related to routing in urban goods distribution as well. With respect specifically to vehicle routing related to e-commerce delivery, the work from Archetti and Bertazzi [23] focuses on routing and inventory routing variants that arise as online orders require fast delivery, leading to characteristics that may differ from classical routing problems. Among additional relevant related works, Moons et al [24] studied the joint problem of order picking and routing vehicles with time windows and release dates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cattaruzza et al [22] surveyed the vehicle routing problems found in cities for good distribution and identified the important challenges related to routing in urban goods distribution as well. With respect specifically to vehicle routing related to e-commerce delivery, the work from Archetti and Bertazzi [23] focuses on routing and inventory routing variants that arise as online orders require fast delivery, leading to characteristics that may differ from classical routing problems. Among additional relevant related works, Moons et al [24] studied the joint problem of order picking and routing vehicles with time windows and release dates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here, many optimization models have been developed following the general vehicle routing problems framework or any of its variants [44,45]. These models may be adjusted and applied to the urban characteristics as in the case of He et al [17] and Archetti and Bertazzi [18]. Additionally, other economics aspects have been included in transportation-related decision-making processes such as the travel time or the cargo efficiency, i.e., the ability to fully load the vehicles.…”
Section: Economic Criterionmentioning
confidence: 99%
“…The last-mile is the last journey of a good to be delivered to the end customer. It has been given a greater focus on logistics strategies because it strongly influences customer satisfaction, time, delivery cost, and ease of use (Archetti and Bertazzi, 2021;Vakulenko et al, 2019). Due to the increasing number of freight vehicles in urban areas, last-mile logistics operations have a considerable impact on three different aspects of sustainability: economic (efficiency and delivery costs), social (congestion and health problems) and environmental (CO 2 emissions and noise pollution) (Janjevic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%